Potensi Gas Biogenik di Cekungan Kutai Bagian Selatan, Kalimantan Timur - Yuyun Yuniardi; Undang Mardiana; Fikri Abdullah (Jurnal Geologi dan Sumberdaya Mineral, 2015)
Delineation of the subsurface of data required to determined potential the presence of biogenic gas. Subsurface interpretation is done by using the data for analysis electrolysis cutting, the log data in the form of Logs GR, RT, NEU, RHOB of 39 wells and gas data (Mud Logs) from the chromatograph and Correlation wells are done. Shallow gas is concentrated or accumulated in the marker interval until Fs-s2 and Fs-s3 (at the depth interval of 950-1300 MSS), and isolated existence.The existence of gas on the platform M in shallow zones (shallow zone, above the marker MF2) is dominated by C1 gas/methane (gas surface), there were no gas C2 (only minor traces on the M38 start at a depth of wells 1200 MSS), while the presence of other gas (C3, C4, C5) only appear as minor traces. Based on gas analysis, it can be concluded that in the interval of 950-1300 MSS there is a surge of the total gas, when compared with data from its Master Log turns anomaly is derived from limestone and coal layers in which these results are correlated with a map of Gas Bearing Reservoir Mapping.Based on the data that has been processed, it can be concluded that the shallow gas accumulates at a depth of 950-1300 MSS or at interval marker Fs-s2 and Fs-s3. So for the next drilling activity on Platform M, is expected to be aware of the depth zone.Keyword - Biogenic Gas, Electrofacies Analysis, Delineation, Gas Analysis, , Marker Interval, Well Correlation